Quantification of β‐aminopropionitrile, an inhibitor of lysyl oxidase activity, in plasma and tumor of mice by liquid chromatography tandem mass spectrometry. (14th January 2014) - Machon, Christelle; Le Calve, Benjamin; Coste, Sylvie; Riviere, Mirella; Payen, Léa; Bernard, David; Guitton, Jérôme
ABSTRACT Lysyl oxidase enzymes are reported to be involved in patho‐physiological process such as tumorigenesis. β‐Aminopropionitrile (BAPN) is an irreversible inhibitor of lysyl oxidase activity, suggesting a potentially useful therapeutic of interest in oncology. This paper describes the first assay concerning the quantification of BAPN by mass spectrometry. A high‐performance liquid chromatography tandem mass spectrometry (LC‐MS/MS) assay was developed for the quantification of BAPN in plasma and tumor of mice. This method combines dansyl chloride (Dns) derivatization and extraction using a solid‐phase extraction Oasis© Max column. Deuterated BAPN was used as internal standard (IS). Separation was achieved using an C18 column HypersylGold, (ThermoElectron), 3.0 µm (100 × 2.1 mm i.d.). Gradient elution with water containing 0.1% acetic acid (A) and acetonitrile containing 0.1% acetic acid (B) was applied. Detection was performed with an electrospray ionization interface operating in negative ion mode. Selected reaction monitoring was used with ion transitions m/z 302 → 249 for BAPN–Dns and m/z 306 → 250 for the IS. The method was fully validated in plasma and was linear and sensitive in the range of 10–500 ng/mL. The lower limit of quantification in plasma was 2.5 ng/mL. This validated assay was successfully applied to a kinetic study of BAPN in mouse plasma and demonstrates that BAPN reaches the tumoral tissue. Copyright © 2014 John Wiley & Sons, Ltd.